1 Ambulatory care visits and admissions for suicidal ideation and self-harm in Canadian adolescents during the COVID-19 pandemic: a population-based analysis. (21st October 2022) - Poonai, Naveen; Freedman, Stephen; Newton, Amanda; Sawyer, Scott; Gaucher, Nathalie; Ali, Samina; Miller, Michael; Mater, Ahmed; Fitzpatrick, Eleanor; Jabbour, Mona; Zemek, Roger; Eltorki, Mohamed; et al.
Abstract: Background: The COVID-19 pandemic has challenged the resiliency of Canada's adolescent population. Understanding changes in mental healthcare utilization can shed light on the impact the pandemic has had on Canada's youth. Objectives: To assess if during the pandemic there has been an increase in the proportion of ambulatory care visits and admissions for suicidal ideation and self-harm among adolescents. Design/Methods: This was a population-based, interrupted time-series analysis of adolescents 10-18 years presenting to an ambulatory care facility (including emergency department) or admitted to a healthcare facility with R458 (suicidal ideation and emotional symptoms), X60-69 (intentional self-poisoning), and X70-84 (intentional self-harm) codes based on the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Canada (ICD-10-CA). We used the National Ambulatory Care Reporting System, Discharge Abstract Database, and Hospital Morbidity Database. The primary outcome was ambulatory care visits for a composite of suicidal ideation, intentional self-poisoning, and intentional self-harm. Results were stratified by age and sex and expressed as a rate (proportion of encounters with an outcome per 100 encounters). We compared the differences (delta) in slopes (average increase in outcomes) between April 1, 2015, to March 31, 2020, and April 1, 2020 to March 31, 2021 to determine if the expected rate (pre-pandemic) differed significantly from the observed rate (pandemic). Results: From April 1, 2020, to March 31, 2021, compared to April 1, 2015, to March 31, 2020, the rate of ambulatory care visits and admissions for all conditions decreased. The average quarterly rate of ambulatory care visits for the composite among males 10-14 years, increased by 40.3%, from 0.57 to 0.8 (slope delta=0.1; 95% CI: 0.02, 0.18; p=0.012). Among females 10-14 years, the rate increased by 85.1%, from 1.81 to 3.35 (slope delta=0.7; 95% CI: 0.43, 0.97; p<0.001). Among males 15-18 years, the rate increased by 29.5%, from 1.56 to 2.02 (slope delta=0.13; 95% CI: -0.02, 0.28; p=0.078). Among females 15-18 years, the rate increased by 33.6%, from 3.18 to 4.25 (slope delta=0.26; 95% CI: -0.16, 0.68; p=0.192). The average quarterly rate of admissions was significant for females 10-14 years and increased by 27.7%, from 8.59 to 10.97 (slope delta=1.99; 95% CI: 0.57, 3.41; p=0.017). Conclusion: The proportion of ambulatory care visits and admissions for emotional symptoms, suicidal ideation, and self-harm during the first year of the COVID-19 pandemic increased compared to pre-pandemic rates among adolescents 10-14 years in Canada. Our findings underscore the importance of promoting public health policies that mitigate the impact of pandemics on adolescent mental health.